The Great Majority of Homologous Recombination Repair-Deficient Tumors Are Accounted for by Established Causes - Štancl, Paula; Hamel, Nancy; Sigel, Keith M.; Foulkes, William D.; Karlić, Rosa; Polak, Paz (Frontiers in Genetics, 2022)
Background: Gene-agnostic genomic biomarkers were recently developed to identify homologous recombination deficiency (HRD) tumors that are likely to respond to treatment with PARP inhibitors. Two machine-learning algorithms that predict HRD status, CHORD, and HRDetect, utilize various HRD-associated features extracted from whole-genome sequencing (WGS) data and show high sensitivity in detecting patients with BRCA1/2 biallelic inactivation in all cancer types. When using only DNA mutation data for detection of potential causes of HRD, both HRDetect and CHORD find that 30% to 40% of cases that have been classified as HRD are due to unknown causes. Here, we examined the impact of tumor-specific thresholds and measurement of promoter methylation of BRCA1 and RAD51C on unexplained proportions of HRD cases across various tumor types. Methods: We gathered published CHORD and HRDetect probability scores for 828 samples from breast, ovarian and pancreatic cancer from previous studies, as well as evidence of their biallelic inactivation (by either DNA alterations or promoter methylation) in HR-related genes. ROC curve analysis evaluated the performance of each classifier in specific cancer. Tenfold nested cross-validation was used to find the optimal threshold values of HRDetect and CHORD for classifying HR deficient samples within each cancer type. Results: With the universal threshold, HRDetect has higher sensitivity in the detection of biallelic inactivation in BRCA1/2 than CHORD and resulted in a higher proportion of unexplained cases. When promoter methylation was excluded, in ovarian carcinoma, the proportion of unexplained cases increased from 26.8% to 48.8% for HRDetect and from 14.7% to 41.2% with CHORD. A similar increase was observed in breast cancer. Applying cancer-type-specific thresholds led to similar sensitivity and specificity for both methods. Cancer-type-specific thresholds for HRDetect reduced the number of unexplained cases from 21% to 12.3% without reducing the 96% sensitivity to known events. For CHORD, unexplained cases were reduced from 10% to 9% while sensitivity increased from 85.3% to 93.9%. Conclusion: These results suggest that WGS-based HRD classifiers should be adjusted for tumor type. When applied, only ~10% of breast, ovarian and pancreas cancer cases are not explained by known events in our dataset.